National Digital Currency Issuance Under Vietnamese Law - The Giang, Vien (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
The article analyzes the current situation and debates about the digital currencies issued by central bank. The results show that only a few countries have issued the central bank digital currencies, the rest of the countries have begun to have institutional orientations for research on issuing and using the central bank digital currency. The strengths that lead to the central bank's choice of research and issuance of digital currency are a high level of security, convenience for money control in circulation, and the stable value guaranteed by the state, thereby contributing to the promotion of non-cash payments. In the context of accelerating the economy digitization, including digital banking, and promoting the cash payments, Vietnam has had an orientation to research mechanisms, policies and laws for the issuance of national digital currency. In order to do this, in addition to reviewing, amending and supplementing the Law on the State Bank of Vietnam related to currency issuance, it is also necessary to prepare fully the technical infrastructure system.